Simultaneous power generation and waste water treatment using microbial fuel cell - Lin, Choo Quan (2013)
Palm Oil Mill Effluent (POME) is one of the major pollutants in Malaysia. Conventional aerobic and anaerobic treatment of wastewater needs more energy to operate it. In this context, treatment of wastewater using Microbial Fuel Cell seems to be promising technology because it reduces operational energy requirement and shows efficient treatment too. This research focused on simultaneous power generation and wastewater treatment by using MFC. The objectives of the study are to study the performance of MFC using Polyacrylonitrile carbon felt (PACF) as electrode and to study the effect of surface area of electrode on coulombic efficiency and Chemcial Oxygen Demand (COD) removal efficiency of MFC. POME was used to harvest energy and reduce COD from complex POME. Different size of PACF was used as electrode for all the experiments. The data collection mode was through observing and recording the voltage, current and power produced by the MFC. The findings were analyzed to obtain optimum power density, coulumbic efficiency and Chemical Oxygen Demand (COD) removal efficiency. Power density, current density and coulombic efficiency of MFC with POME were calculated. Comparing the results obtained and calculated, MFC with PACF surface area (34.79cm2) showed the highest value for maximum power density of about 76.2133 mW/m2, coulumbic effiency of 0.9561% and COD removal efficiency of 45.6%.